Pemurnian Minyak Jelantah Menggunakan Adsorben Natural Teraktivasi H2SO4 dengan Operasi Shaker - Fithry, Dwi Annisa; Haryanto, Bode; Siregar, Durain P; Albanna, Fikry (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Indonesia is recognized as the world's leading producer of palm oil (Elaeis guineensis Jacq.), which contributes to a substantial accumulation of oil palm biomass waste. Among these, oil palm fronds present a promising potential as low-cost and eco-friendly adsorbent materials. Concurrently, the repeated use of cooking oil generates used cooking oil, a waste product that poses significant health risks due to the accumulation of harmful compounds. This study explores the application of oil palm frond-based adsorbents for the purification of used cooking oil through an adsorption mechanism. Experimental results revealed that the optimal adsorbent performance was achieved using 4.5 grams of adsorbent with a particle size of 100 mesh, which successfully reduced the turbidity of used cooking oil to 28.5 NTU, with a total adsorbed turbidity value of 95.5 NTU. Kinetic modeling indicated that the adsorption process followed a pseudo-second-order model, supported by a high correlation coefficient (R² = 0.9983), suggesting that the adsorption mechanism is dominated by chemisorption involving chemical interactions between the adsorbent surface and the contaminants in the oil.